Light Inhibition of Shoot Regeneration Is Regulated by Endogenous Abscisic Acid Level in Calli Derived from Immature Barley Embryos. - Kazuhide Rikiishi; Takakazu Matsuura; Yoko Ikeda; Masahiko Maekawa (PLoS ONE)
Shoot regeneration in calli derived from immature barley embryos is regulated by light conditions during the callus-induction period. Barley cultivars Kanto Nijo-5 (KN5) and K-3 (K3) showed lower efficiency of shoot regeneration in a 16-h photoperiod during callus-induction than those in continuous darkness, whereas shoot regeneration was enhanced in cultures under a 16-h photoperiod in Golden Promise (GP) and Lenins (LN). These cultivars were classified as photo-inhibition type (KN5 and K3) or photo-induction type (GP and LN) according to their response to light. Contents of endogenous plant hormones were determined in calli cultured under a 16-h photoperiod and continuous darkness. In photo-inhibition type, higher accumulation of abscisic acid (ABA) was detected in calli cultured under a 16-h photoperiod, whereas calli showed lower levels of endogenous ABA in continuous darkness. However, cultivars of photo-induction type showed lower levels of ABA in calli cultured under both light conditions, similarly to photo-inhibition type in continuous darkness. Exogenous ABA inhibited the callus growth and shoot regeneration independent of light conditions in all cultivars. In photo-inhibition type, lower levels of endogenous ABA induced by ABA biosynthesis inhibitor, fluridone, reduced the photo-inhibition of shoot regeneration. Expression of ABA biosynthesis gene, HvNCED1, in calli was regulated by the light conditions. Higher expression was observed in calli cultured under a 16-h photoperiod. These results indicate that ABA biosynthesis could be activated through the higher expression of HvNCED1 in a 16-h photoperiod and that the higher accumulations of ABA inhibit shoot regeneration in the photo-inhibition type cultivars.